2009
DOI: 10.1021/jp9008702
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Structure and Property of Pt-Decorated Nanoporous Gold by Thermal Annealing

Abstract: We study the structure evolution of a novel electrocatalyst, Pt-decorated nanoporous gold (Pt-NPG), during thermal annealing at relatively low temperatures. Pt-NPG was made by plating a thin layer of Pt over NPG substrate during an electroless plating process that generated epitaxial Pt nanoislands loaded on the NPG surface. In comparison with Pt’s very high melting point, thermal annealing at temperatures as low as 100 °C was found to significantly change the structure and surface chemistry of these nanomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 32 publications
4
51
0
Order By: Relevance
“…3(d)-(f)) becomes more and more obvious. It is well known that the stripping peak profile is sensitive to the composition and microstructure of metal particles [30], and several studies have found that the CO stripping curves associated with the Au-Pt [31,32], Pd-Ag [33], Pd-Ir [34], and Pt-Ru-P [35], will exhibit a contour change by variating the amount of the additive elements. Thus, the appearing shoulder peak may be caused by the existing residual Al in the Pd rods ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3(d)-(f)) becomes more and more obvious. It is well known that the stripping peak profile is sensitive to the composition and microstructure of metal particles [30], and several studies have found that the CO stripping curves associated with the Au-Pt [31,32], Pd-Ag [33], Pd-Ir [34], and Pt-Ru-P [35], will exhibit a contour change by variating the amount of the additive elements. Thus, the appearing shoulder peak may be caused by the existing residual Al in the Pd rods ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 The weak peak O 1 at 0.55 V and the strong peak O 2 at 0.9 V on the Pt/C electrocatalyst correspond to the direct dehydrogenation oxidation and indirect dehydration oxidation of formic acid, respectively (Fig. [27][28][29][30][31][32][33][34][35][36][37][38][39] The isolated Pt atom facilitates the direct dehydrogenation pathway of the FAOR (i.e., the ensemble effect). The ratio of the two peak currents (IO 1 /IO 2 ) is calculated to be 0.22, indicating that the FAOR on the Pt/C electrocatalyst occurs mainly through the indirect dehydration pathway.…”
Section: Electrocatalytic Testsmentioning
confidence: 99%
“…The enhanced electrocatlytic activity of Pt n /GNN composites is attributed to the domination of the direct oxidation of formic acid [23,25]. Cuesta et al [20] demonstrated that the direct oxidation of formic acid does not involve the adsorption of CO by using ATR-SEIRAS and HCOO ad is directly oxidized to CO 2 , which explains why Pt n /GNN composites have better stabilities than Pt/C, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%